Religious Development of Students as an Effort To Prevent Radicalism In High Schools In Bandung - Yayah Fijriyah; Agus Salim Mansyur; Supiana Supiana; Nina Nurmila (Journal of Social Science, 2021)
This study aims to describe religious development as an effort to prevent radicalism in students at SMAN 10 and SMA Karya Pembangunan 2 Bandung. This study uses a qualitative approach with a descriptive method. Data collection techniques through interviews, observation and documentation. Data analysis techniques using data analysis techniques consisting of data reduction, data presentation, and conclusions. There are three findings, namely: (1) PAI teachers' perceptions of religious radicalism are twofold, namely a) radicalism is seen as thought b) religious radicalism is seen as action. (2) Factors Affecting Teachers' Perceptions of Religious Radicalism there are two factors, namely factors originating from the perceiver (PAI teachers) and the situation. (3) The preventive efforts of PAI teachers in both schools against the issue of religious radicalism in students are divided into two scopes, namely inside the classroom and outside the classroom. The scope of the class has three efforts, namely (a) Islamic religious education subject matter on the issue of religious radicalism has been discussed by the teacher in the classroom, (b) various learning methods by raising the issue of religious radicalism and tolerance in society, the teacher uses learning methods namely lectures, question and answer, sociodrama and practice, (c) students' knowledge of religious radicalism is diverse and dynamic. Meanwhile . Outside the classroom, the efforts include (a) prayer before and after learning, (b) congregational prayers, (c) religious extracurricular activities, (d) anti-violence task force, (e) creating tolerance in schools.